Five-Year Outcomes of Short-Term Radiotherapy Plus Chemotherapy Versus Long-Term Chemoradiotherapy for Locally Advanced Rectal Cancer: Updated Results of the STELLAR Trial - Yuan Tang; Hai-Tao Zhou; Tong-Zhen Xu; Ning Li; Li-Ming Jiang; Jun Jiang; Ning-Ning Lu; Shuai Li; Si-Lin Chen; Hui-Ying Ma; Yong Cai; Yong-Heng Li; et al. (Journal of Clinical Oncology, 2026)
This updated analysis of the STELLAR trial reports 5-year outcomes comparing short-course radiotherapy followed by chemotherapy (SCRT-based total neoadjuvant therapy [TNT]) with standard long-course chemoradiotherapy (CRT) in patients with locally advanced rectal cancer (LARC). Patients with distal or middle-third LARC were randomly assigned to receive either SCRT-based TNT or CRT. At a median follow-up of 68.7 months, the 5-year disease-free survival (DFS) was 62.0% in the TNT group and 58.7% in the CRT group, with a hazard ratio (HR) for DFS of 0.849 (95% CI, 0.662 to 1.089). Five-year overall survival (OS) was significantly higher with TNT (78.1% v 69.7%; HR, 0.739 [95% CI, 0.550 to 0.993]). Distant metastasis (DM) and locoregional recurrence (LRR) rates were similar between the two groups. In high-risk patients (per European Society for Medical Oncology criteria), TNT was associated with improved OS (HR, 0.663 [95% CI, 0.469 to 0.937]) and showed a nonsignificant trend toward improved DFS (HR, 0.765 [95% CI, 0.568 to 1.032]). In patients with DM or LRR, TNT was associated with both improved postrecurrence progression-free survival (HR, 0.691 [95% CI, 0.497 to 0.961]) and postrecurrence survival (HR, 0.698 [95% CI, 0.490 to 0.994]). These results suggest that SCRT-based TNT provides a durable survival advantage and is a viable alternative to CRT, especially in patients with high-risk disease.